Analisis Efektivitas Pengembangan Bahan Ajar Fisika dengan Konten Kecerdasan Emosional Pada Materi Vektor dan Gerak Lurus Untuk Kelas X SMA/MA - Hanisa Ayudia Saleh; Zulhendri Kamus; Gusnedi Gusnedi (PILLAR OF PHYSICS EDUCATION, 2018)
Curriculum 2013 has four core competencies to be achieved consisting of spiritual competence, social attitude competence, knowledge competence, and skill competence. But in reality it is not as expected. One factor is the lack of use of learning resources that can improve the competence of studens in accordance with the demands of the curriculum 2013. This study aims to design a product in the form of learning materials that contain content of emotional intelligence values on Physics materials about addition vectors and linear motion. The type of research is research and development (R & D). In this study there are 10 steps, namely potential and problems, data collection, design, product testing, design revision, trial usage, product revision, mass product. However, in this study only done until the third stage, the product design is doing research to make the product design but not followed by making and testing the product. The results of this study based on the analysis that has been done is a descriptive product of physics learning materials that are charged emotional intelligence values based on the meaning of materials and concepts of Physics on the topic of vector and linear motion for the imple- mentation of curriculum 2013 on the learning of class X / SMA / MA students.